Impact of βn and spectrum of n = 1 applied fields on fast ion losses in DIII-D. (1st March 2023) - Gage, K.R.; Chen, X.; Van Zeeland, M.; Heidbrink, W.W.; Hanson, J.; Lyons, B.; Pace, D.C.; Galdon-Quiroga, J.; Garcia-Munoz, M.
Abstract: The effect of n = 1 magnetic perturbations (MPs) on prompt fast ion losses in DIII-D has been investigated using the light ion beam probe technique. The effect of normalized beta, β n, and the plasma response to the MPs is studied for several MP spectra. Magnetics data show a strong dependence of plasma response to β n that depends on the phase difference in perturbation coils, Δ ϕ U L . For most phases, the response increases with β n, however, the response is suppressed for phases between 180 ∘ and 240 ∘ . Experimental data from scintillator based fast ion loss detectors shows that relative fluctuation of lost ions (20%–30% of the steady signal) does not diminish across the L- to H-mode transition for Δ ϕ U L = 240 ∘, despite the 34% decrease in radial response field and 50% decrease in poloidal response field. Simulations of the DIII-D discharges using M3D-C1 and ASCOT5 find that prompt losses from neutral beam injection in each investigated case hit the first wall at several concentrated locations: the vessel floor, midplane diagnostic ports, vessel ceiling, and inner wall. Simulated losses from co-injection neutral beams are born outside the last closed flux surface, corresponding to radial orbit displacements of 3–6 cm due to the MPs.